2014
DOI: 10.4025/actasciagron.v36i3.16281
|View full text |Cite
|
Sign up to set email alerts
|

<b>Distribution of the root system of peach palm under drip irrigation

Abstract: ABSTRACT. The incorporation of technologies has resulted in increased productivity and the more rational management of peach palm, with irrigation being an important tool for certain regions. Thus, studies leading to proper crop management are extremely important, such as the estimate of the effective depth of the root system, which is indispensable for proper irrigation management. The objective of this study was to evaluate the effects of different irrigation depths, as applied by drip irrigation, on the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…As Pereira (2011) discusses, localized irrigation that creates wet bulb in the soil induces the concentration of roots around points where water is applied. By watering the papaya plants with drip irrigation, Coelho et al (2005) verified that 80% of roots were concentrated in the first 0.45 m in depth, while Lopes et al (2014) reported that 90% of the roots of peach-palm watered by drip irrigation are found at depths from 0 to 0.30 m, indicating that 0.3 m is the effective depth of the root system for irrigation purposes.…”
Section: Resultsmentioning
confidence: 99%
“…As Pereira (2011) discusses, localized irrigation that creates wet bulb in the soil induces the concentration of roots around points where water is applied. By watering the papaya plants with drip irrigation, Coelho et al (2005) verified that 80% of roots were concentrated in the first 0.45 m in depth, while Lopes et al (2014) reported that 90% of the roots of peach-palm watered by drip irrigation are found at depths from 0 to 0.30 m, indicating that 0.3 m is the effective depth of the root system for irrigation purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Tabela 5 -Comparação de médias entre adubações utilizadas em cultivo do híbrido de eucalipto Grancam para os atributos altura de plantas (ALT), diâmetro à altura do peito (DAP), volume de madeira (VOL) em Aquidauana-MS. Em relação ao DAP, as adubações realizadas em sistemas irrigados, propiciaram maiores taxas de crescimento mensais até o 45° MAP, mas não se diferiram estatisticamente da adubação convencional na área sem irrigação, nos últimos períodos avaliados (50° e 53° MAP) (Tabela 5). Possivelmente influenciado pelo aumento das chuvas na região, o que possibilitou às plantas da Pereira, V. G. M. F.;Lopes, A. S.;Belchior, I. B.;Fanaya Júnior, E. D.;Pacheco, A.;Brito, K. R. M. 1111 AD-SI aumentar o crescimento em DAP, visto, que, plantas não irrigadas exploram um maior volume solo, quando comparadas às submetidas à irrigação.…”
Section: Resultsunclassified
“…Neste contexto, alguns autores evidenciam esse comportamento. Segundo Lopes et al (2014), as raízes da pupunheira possuem melhor distribuição na ausência de irrigação. Corroborando Covre et al (2015), que observaram que as plantas de Coffea canephora não irrigadas apresentam maiores comprimentos e volume de raízes, por volume de solo, quando comparadas às plantas irrigadas.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Swine breeding on country comes developing rapidly for as recent decades. The animals number increase results in higher production of swine wastewater, as well as the environmental impacts (Guimarães et al, 2017;Lopes et al, 2014;Yuan et al, 2018). This activity is considered potentially pollutant because it uses a lot of water in its production process, generating a large slurry volume (Sousa et al, 2014;Yuan et al, 2018) The swine wastewater can represent an important fertilizer or potential environmental risk, depending on how the resource is managed (Boitt et al, 2018;Egewarth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%